OBJEKTIFIKASI TUBUH LAKI-LAKI DALAM EKSPRESI SEKSUAL PEREMPUAN DI MEDIA SOSIAL - Astari, Ayang (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2022)
This research aims, among others: (1) How is the form of expression of women in objectifying the male body on social media, (2) Knowing the responses and opinions of some users who see the objectification of the male body on social media. The method used in this research is descriptive qualitative method, with a phenomenological approach. With data collection through non-participant observation in Twitter social media. Based on the results of the study, it can be concluded that women basically also have the same sexual desires but have their own ways of conveying their sexual expressions. The results in this study show: (1) Through social media they give forms of expression with sensual language such as, the desire to be raped, to declare their uterus warm just by looking at a man's body image. (2) Differences in perception between the pros and cons of the reality that occurs in social media, but the perception of other social media users chooses to be against the actions taken by women in social media.